PENGARUH PENAMBAHAN BAHAN CAMPURAN TEMPURUNG KELAPA TERHADAP KINERJA GASIFIKASI SEKAM PADI MENGGUNAKAN UPDRAFT GASIFIER - , RAHADIAN WIDI ASTARA, Dr. Ir. Bambang Purwantara, M.Agr. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Gasification is a technology or a way to convert solid biomass into energy in the form of gas. Husk gasification has been carried out and there is a material reduction in the rate of problems one of them. One way of dealing with mixing coconut shell. This research was conducted to determine the effect of mixing coconut shell on the performance of rice husk gasification using updraft gasifier. Research was conducted with a mixture of coconut shell gives the variation of 0%, 5%, 10%, 15% and 20%. The results were compared with the performance of gasification on loading 10 kg and 20 kg. Parameters of gasifier performance are temperature of the stove and the reactor, the rate of decrease in the material, the volume of tar, the rest mass gasification and effective flame. The results showed that treatment of the giving of a mix of ingredients can improve the performance of the updraft gasifier from aspect of the decline of the better material of 0.25 cm/minutes to 0.32 cm/minutes which means that the cavity can be resolved so that the gasification is going well. From the results of measurements of the best on the load of 0 kg which is equivalent to a mixture of 0% at a load of 10 kg and 20 kg invariation of the mix of coconut shell and rice husk is the composition of 10%: 90% for the stove temperature, reactor temperature, residual gasification and effective flame. While the composition of 15%: 85% for the rate of decline material and volume of tar. Key word: gasification, rise husk, coconut shell, performance, mixing.